Paleoecology of the late Pleistocene avifauna from Marlera (Istria, Croatia) with notes on the voles record - Ankica Oros Sršen; Vibor Novak; Mateo Petrović; Emily Tilby; Jadranka Mauch Lenardić; Preston T. Miracle (Quaternary International, 2026)

Friability of pelletized biosolids thermally dried from various types of anaerobically digested sludges with and without thermal hydrolysis pretreatment - Yitao Li; Dian Zhang; John T. Novak; Robin Burch; Alex Novak; Zhi-Wu Wang (Waste Management, 2026)

Use of atypical plant resources for cattle farming in Western Europe to drive agroecological transition - T. Puech; A. Farruggia; D. Durant; J.F. Glinec; S. Novak; F. Signoret; F. Stark; D. Sterling (Agricultural Systems, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P02-11 Enhancing genotoxicity assessment: advanced 3D cell models for chemical testing - I. Durmišević; A. Haverić; M. Štampar; S. Žabkar; M. Hadžić Omanović; T. Ćetković Pećar; A. Štern; K. Kološa; M. Novak; K. Fras; S. Haverić; B. Žegura (Toxicology Letters, 2024)

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

Interdisciplinary design of a fish ramp using migration routes analysis - Gorazd Novak; Polona Pengal; Ana T. Silva; José M. Domínguez; Angelo Tafuni; Matjaž Četina; Dušan Žagar (Ecological Modelling, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Anti-neoplastic pharmacophore benzophenone-1 coumarin (BP-1C) targets JAK2 to induce apoptosis in lung cancer - Ankith Sherapura; Vikas H. Malojirao; Prabhu Thirusangu; B. S. Sharath; Shivananda Kandagalla; V. Vigneshwaran; Jurica Novak; Lakshmi Ranganatha; Y. L. Ramachandra; Shrinath M. Baliga; Shaukath Ara Khanum; B. T. Prabhakar (Apoptosis, 2022)

Correction to: Eelgrass Genetic Diversity Influences Resilience to Stresses Associated with Eutrophication - Holly K. Plaisted; Alyssa B. Novak; Sarah Weigel; Anita S. Klein; Frederick T. Short (Estuaries and Coasts, 2020)

Eelgrass Genetic Diversity Influences Resilience to Stresses Associated with Eutrophication - Holly K. Plaisted; Alyssa B. Novak; Sarah Weigel; Anita S. Klein; Frederick T. Short (Estuaries and Coasts, 2020)

Coarse- and fine-scale acoustic telemetry elucidates movement patterns and temporal variability in individual territories for a key coastal mesopredator - Sarah L. Becker; John T. Finn; Ashleigh J. Novak; Andy J. Danylchuk; Clayton G. Pollock; Zandy Hillis-Starr; Ian Lundgren; Adrian Jordaan (Environmental Biology of Fishes, 2020)

Simultaneous energy generation and UV quencher removal from landfill leachate using a microbial fuel cell - Syeed Md Iskander; John T. Novak; Brian Brazil; Zhen He (Environmental Science and Pollution Research, 2017)

17β-Estradiol influent and effluent concentrations in wastewater: demographic influences and the risk to environmental health - K. T. Heffron; K. F. Gaines; J. M. Novak; T. Canam; D. A. Collard (Environmental Monitoring and Assessment, 2016)

Biochar’s role as an alternative N-fertilizer: ammonia capture - Kurt A. Spokas; Jeff M. Novak; Rodney T. Venterea (Plant and Soil, 2012)

Leaf reddening in the seagrass Thalassia testudinum in relation to anthocyanins, seagrass physiology and morphology, and plant protection - Alyssa B. Novak; Frederick T. Short (Marine Biology, 2011)

Vertical Distribution of Corn Stover Dry Mass Grown at Several US Locations - Wally W. Wilhelm; Jane M. F. Johnson; Dave T. Lightle; Douglas L. Karlen; Jeff M. Novak; Nancy W. Barbour; David A. Laird; John Baker; Tyson E. Ochsner; Ardell D. Halvorson; David W. Archer; Francisco Arriaga (BioEnergy Research, 2011)

Nutrient Removal as a Function of Corn Stover Cutting Height and Cob Harvest - Jane M. F. Johnson; Wally W. Wilhelm; Douglas L. Karlen; David W. Archer; Brian Wienhold; David T. Lightle; David Laird; John Baker; Tyson E. Ochsner; Jeff M. Novak; Ardell D. Halvorson; Francisco Arriaga; et al. (BioEnergy Research, 2010)

Benefits of Supplementation of an Electrolyte Scour Treatment with a Bacillus-Based Direct-Fed Microbial for Calves - C. A. Wehnes; K. N. Novak; V. Patskevich; D. R. Shields; J. A. Coalson; A. H. Smith; M. E. Davis; T. G. Rehberger (Probiotics and Antimicrobial Proteins, 2009)

Potato, Solanum Tuberosum, Defense Against Colorado Potato Beetle, Leptinotarsa Decemlineata (Say): Microarray Gene Expression Profiling of Potato by Colorado Potato Beetle Regurgitant Treatment of Wounded Leaves - Susan D. Lawrence; Nicole G. Novak; Chelsea J.-T. Ju; Janice E. K. Cooke (Journal of Chemical Ecology, 2008)

Effect of soil water stress on soil respiration and its temperature sensitivity in an 18‐year‐old temperate Douglas‐fir stand - RACHHPAL S. JASSAL; T. ANDREW BLACK; MICHAEL D. NOVAK; DAVID GAUMONT‐GUAY; ZORAN NESIC (Global Change Biology, 2008)
We analyzed 17 months (August 2005 to December 2006) of continuous measurements of soil CO 2 efflux or soil respiration ( R S ) in an 18‐year‐old west‐coast temperate Douglas‐fir stand that experienced somewhat greater than normal summertime water deficit. For soil water content at the 4 cm depth ( θ ) > 0.11 m 3 m −3 (corresponding to a soil water matric potential of −2 MPa), R S was positively correlated to soil temperature at the 2 cm depth ( T S ). Below this value of θ , however, R S was largely decoupled from T S , and evapotranspiration, ecosystem respiration and gross primary productivity (GPP) began to decrease, dropping to about half of their maximum values when θ reached 0.07 m 3 m −3 . Soil water deficit substantially reduced R S sensitivity to temperature resulting in a Q 10 significantly R S (i.e. d R S /d T S ) increased with θ up to 0.15 m 3 m −3 , above which it slowly declined. The value of d R S /d T S was nearly 0 for θ 3 m −3 , thereby confirming that R S was largely unaffected by temperature under soil water stress conditions. Despite the possible effects of seasonality of photosynthesis, root activity and litterfall on R S , the observed decrease in its temperature sensitivity at low θ was consistent with the reduction in substrate availability due to a decrease in (a) microbial mobility, and diffusion of substrates and extracellular enzymes, and (b) the fraction of substrate that can react at high T S , which is associated with low θ . We found that an exponential (van't Hoff type) model with Q 10 and R 10 dependent on only θ explained 92% of the variance in half‐hourly values of R S , including the period with soil water stress conditions. We hypothesize that relating Q 10 and R 10 to θ not only accounted for the effects of T S on R S and its temperature sensitivity but also accounted for the seasonality of biotic (photosynthesis, root activity, and litterfall) and abiotic (soil moisture and temperature) controls and their interactions.

Effect of adenoviral mediated overexpression of fibromodulin on human dermal fibroblasts and scar formation in full-thickness incisional wounds - Alexander Stoff; Angel A. Rivera; J. Michael Mathis; Steven T. Moore; N. S. Banerjee; Maaike Everts; Antonio Espinosa-de-los-Monteros; Zdenek Novak; Luis O. Vasconez; Thomas R. Broker; Dirk F. Richter; Dale Feldman; et al. (Journal of Molecular Medicine, 2007)

Arbuscular mycorrhiza alter the concentration of essential oils in oregano (Origanum sp., Lamiaceae) - T. Khaosaad; H. Vierheilig; M. Nell; K. Zitterl-Eglseer; J. Novak (Mycorrhiza, 2006)

Element Levels in Snakes in South Carolina: Differences Between a Control Site and Exposed Site on the Savannah River Site - J. Burger; S. Murray; K. F. Gaines; J. M. Novak; T. Punshon; C. Dixon; M. Gochfeld (Environmental Monitoring and Assessment, 2006)

Different patterns of the L-histidine decarboxylase (HDC) gene expression in mice resistant and susceptible to experimental cutaneous leishmaniasis - Z. Ps; K. Mller; I. Novak; E. Buzs; W. Solbach; A. Falus; T. Laskay (Inflammation Research, 2004)

Iron precipitation kinetics in synthetic acid mine drainage - Harry R. Diz; John T. Novak; J. Donald Rimstidt (Mine Water and the Environment, 1999)

Effects of climatic variability on the annual carbon sequestration by a boreal aspen forest - W. J. Chen; T. A. Black; P. C. Yang; A. G. Barr; H. H. Neumann; Z. Nesic; P. D. Blanken; M. D. Novak; J. Eley; R. J. Ketler; R. Cuenca (Global Change Biology, 1999)
To evaluate the carbon budget of a boreal deciduous forest, we measured CO 2 fluxes using the eddy covariance technique above an old aspen (OA) forest in Prince Albert National Park, Saskatchewan, Canada, in 1994 and 1996 as part of the Boreal Ecosystem‐Atmosphere Study (BOREAS). We found that the OA forest is a strong carbon sink sequestering 200 ± 30 and 130 ± 30 g C m –2 y –1 in 1994 and 1996, respectively. These measurements were 16–45% lower than an inventory result that the mean carbon increment was about 240 g C m –2 y –1 between 1919 and 1994, mainly due to the advanced age of the stand at the time of eddy covariance measurements. Assuming these rates to be representative of Canadian boreal deciduous forests (area ≈ 3 × 10 5 km 2 ), it is likely they can sequester 40–60 Tg C y –1 , which is 2–3% of the missing global carbon sink. The difference in carbon sequestration by the OA forest between 1994 and 1996 was mainly caused by the difference in leaf emergence date. The monthly mean air temperature during March–May 1994, was 4.8 °C higher than in 1996, resulting in leaf emergence being 18–24 days earlier in 1994 than 1996. The warm spring and early leaf emergence in 1994 enabled the aspen forest to exploit the long days and high solar irradiance of mid‐to‐late spring. In contrast, the 1996 OA growing season included only 32 days before the summer solstice. The earlier leaf emergence in 1994 resulted 16% more absorbed photosynthetically active radiation and a 90 g C m –2 y –1 increase in photosynthesis than 1996. The concomitant increase in respiration in the warmer year (1994) was only 20 g C m –2 y –1 . These results show that an important control on carbon sequestration by boreal deciduous forests is spring temperature, via the influence of air temperature on the timing of leaf emergence.

Turbulent Flux Measurements Above and Below the Overstory of a Boreal Aspen Forest - P.D. Blanken; T. A. Black; H. H. Neumann; G. Den Hartog; P. C. Yang; Z. Nesic; R. Staebler; W. Chen; M. D. Novak (Boundary-Layer Meteorology, 1998)

Coherent eddies and temperature structure functions for three contrasting surfaces. Part II: Renewal model for sensible heat flux - Wenjun Chen; Michael D. Novak; T. Andrew Black; Xuhui Lee (Boundary-Layer Meteorology, 1997)

Coherent eddies and temperature structure functions for three contrasting surfaces. Part I: Ramp model with finite microfront time - Wenjun Chen; Michael D. Novak; T. Andrew Black; Xuhui Lee (Boundary-Layer Meteorology, 1997)

Altered secretion of kidney lysosomal enzymes in the mouse pigment mutants ruby-eye, ruby-eye-2-J, and maroon - Edward K. Novak; Frederick Wieland; Gerald P. Jahreis; Richard T. Swank (Biochemical Genetics, 1980)